Estudo teórico-experimental de propriedades físico químicas do cocristal L-triptofano-(e)-ácido-2-butenodióico hidratado - RIBEIRO, Francisco Dânio Cornélio (2024)
In this study, single crystals of L-tryptophan-fumaric acid-water (LTFAW) were obtained using the slow solvent evaporation method, while LTFAW polycrystals were synthesized by mechanochemical method. The physicochemical properties, including electrostatic potential maps and vibrational analysis, were investigated using density functional theory (DFT). Structural and vibrational properties were elucidated through powder X-ray diffraction (PXRD), Raman spectroscopy, and infrared spectroscopy (FT-IR). Hirshfeld surface analysis was performed using the CIF file format, and molecular docking studies were conducted to predict the interaction of LTFAW with the active site of the Cyclooxygenase-2 (COX-2) protein. The results demonstrated that the mechanochemical synthesis process offered significant advantages over the conventional slow evaporation method, including higher yield, reduced synthesis time, and decreased solvent consumption. Structural studies by PXRD indicated that LTFAW crystallizes in a monoclinic crystal system with space group C2 (P21), and Rietveld refinements revealed good agreement with reported standards. DFT calculations were consistent with experimental data, supporting the reliable assignment of IR and Raman bands, and enabling the elucidation of electronic properties of LTFAW trimers through electrostatic potential maps, highlighting nucleophilic and electrophilic regions. Reactivity indices calculated for the precursors suggested good chemical stability, indicating that the material formed through the interaction of fumaric acid and L-tryptophan molecules may exhibit interesting biological properties. Theoretical IR and Raman spectra aligned well with experimental results, and Hirshfeld surface analysis identified hydrogen bonds (O⋯H) as the primary interactions responsible for atomic packing in the crystal lattice. Molecular docking studies suggested that LTFAW has a binding free energy (-10.68 kcal·mol⁻¹) and inhibition constant (1.48e+01) more favorable than commercial inhibitors Ketorolac, Indomethacin, Celecoxib, and Etodolac, as well as the fumaric acid and L-tryptophan precursors. Key ligand-receptor interactions included π-sigma (VAL-523), π-alkyl (LEU-352, ALA-527, and VAL-349), and hydrogen bonds (GLY-526), suggesting that LTFAW could be an effective alternative as a COX-2 enzyme inhibitor.